Urological Carcinomas in Patients Presenting with Gross Haematuria: A Retrospective Study of 155 Cases - Mudassar Saeed Pansota, Rashid Bin Hamid, Adnan Khan, Muhammad Junaid, Ajmal Khan Bazai, Jamshed Khan, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Gross haematuria is a significant clinical symptom that often indicates urological malignancy, including bladder cancer, renal cell carcinoma (RCC), and urothelial carcinoma of the renal pelvis and ureter. Early identification and diagnosis are crucial for optimal treatment outcomes. This study aims to investigate the types of urological malignancies in patients presenting with gross haematuria. Methods: A retrospective analysis of 155 patients who presented with gross haematuria between January 2017 and October 2023 was conducted. Clinical, imaging, and histopathological data were reviewed for the diagnosis of urological malignancies. Results: Bladder cancer was the most common malignancy (49%), followed by RCC (30%) and urothelial carcinoma of the renal pelvis (14%). Cystoscopy and CT urography were the primary diagnostic modalities. Smoking and occupational exposure were significant risk factors. Logistic regression identified smoking as the strongest predictor of bladder cancer. Conclusion: Gross haematuria is a key symptom that should lead to early and thorough evaluation for urological cancers, particularly bladder cancer. Timely use of imaging and cystoscopy improves diagnostic accuracy. Keywords: gross haematuria, urological carcinoma, bladder cancer, renal cell carcinoma, urothelial carcinoma, diagnostic modalities